Transradial Embolization of Hemorrhagic Adrenal Myelolipoma - Griffin Mcnamara; Ahmed Abdelbaki; Jeremy Mccarver; David Owens; Ali Malik; Keith Pereira; Alejandro Mendez (The Arab Journal of Interventional Radiology)
Adrenal myelolipomas are largely benign, non-functioning, and asymptomatic adrenal tumors found incidentally on imaging. These tumors have an extremely low incidence and are exceedingly rare. We report a case of trans-radial embolization of hemorrhagic adrenal myelolipoma.